Cities in Caribbean Literature: a study of V. S. Naipaul’s Miguel Street and Jamaica Kincaid’s A Small Place - Masud, Farhin Al (BRAC University, 2018)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2018.